2006
DOI: 10.1038/sj.cr.7310010
|View full text |Cite
|
Sign up to set email alerts
|

uPAR expression under hypoxic conditions depends on iNOS modulated ERK phosphorylation in the MDA-MB-231 breast carcinoma cell line

Abstract: Urokinase plasminogen activator receptor (uPAR) plays a major role in cancer invasion and metastasis and uPAR expression is correlated with a poor prognosis in various cancer types. Moreover, the expression of uPAR is increased under hypoxic conditions. Nitric oxide (NO) and its metabolites produced by inducible nitric oxide synthase (iNOS) are important products of hypoxic stress, and NO may activate or modulate extracellular signal regulated kinase (ERK). Here, we evaluated uPA, uPAR, and activated ERK level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
0
22
0
1
Order By: Relevance
“…The present study showed that increased tumor hypoxia associated with up-regulation of metastasisrelated genes such as uPA, c-met, PDGF-A, and IL-8 as well as relatively more CTCs. It has been reported that c-met, uPA, and IL-8 expression regulated by hypoxia facilitated movement of tumor cells into the circulation, thus increasing the number of CTCs (Pennacchietti et al 2003;Mizukami et al 2005;Yoon et al 2006). The increased expression of hypoxia-related invasive factors induced by IFN-could render the tumor to be more invasive by escaping the primary site.…”
Section: Discussionmentioning
confidence: 96%
“…The present study showed that increased tumor hypoxia associated with up-regulation of metastasisrelated genes such as uPA, c-met, PDGF-A, and IL-8 as well as relatively more CTCs. It has been reported that c-met, uPA, and IL-8 expression regulated by hypoxia facilitated movement of tumor cells into the circulation, thus increasing the number of CTCs (Pennacchietti et al 2003;Mizukami et al 2005;Yoon et al 2006). The increased expression of hypoxia-related invasive factors induced by IFN-could render the tumor to be more invasive by escaping the primary site.…”
Section: Discussionmentioning
confidence: 96%
“…The literature has shown that HIF-1A activation promotes transcriptional activation of uPAR in cancer cells (48,70,71), thereby indicating that a mutual regulatory mechanism exists between HIF-1A and uPAR signaling mechanisms, which regulates the angiogenesis tube-inducing ability and adaptation to radiation treatment of both cancer cells and CSCs (Fig. 5F).…”
Section: Discussionmentioning
confidence: 99%
“…The mitogen-activated protein kinases kinase (MEK)/extracellular signal-regulated kinases (ERKs) signaling cascade plays an important role in the differentiation of MSCs (Joannides et al 2003;Jaiswal et al 2000). Treatment of adult human MSCs with osteogenic conditioned medium results in sustained ERK activation, whereas the inhibition of ERK activation blocks osteogenic differentiation in a dose-dependent manner, as does transfection with a dominant negative form of MEK, an upstream kinase regulating ERK (Jaiswal et al 2000;Yoon et al 2006;Yang et al 2006;Guerriero et al 2006). Moreover, activation of ERK contributes to the induction of cell migration and epithelial-mesenchymal transition (Irie et al 2005).…”
Section: Introductionmentioning
confidence: 99%